The Discovery of the Self Through the Academic Sojourn (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
This paper draws on findings taken from an ethnographic study of the adjustment experiences of international postgraduate students to illuminate the process of change undergone by sojourners. It is observed that exposure to a new culture and distance from the origin culture act as a catalyst for change: students described themselves as more culturally aware, more independent, more confident, and more assertive. Although such change is cast in the literature and indeed by informants themselves as a positive evolution, this paper notes that the imminence of re-entry to the origin culture represents a source of apprehension as the fit between original cultural norms and the modified self is questioned. Key words Academic sojourn, tolerance, independence, strength, assertiveness, apprehension